European integration and the clash of civilizations - Pavilionis, Žygimantas (Politologija, 1999)
Recently, on March 12, 1998, the British Foreign Secretary Robin Cook announced the day to be "a historic date, save contemporary and the future member-states of the European Union, Europe, once and for long decades divided, have come together into unity". By saying this, the Foreign Secretary touched upon a pressing issue of today, namely, the question - what is Europe on this day?In this context, in the process of European integration after the Cold War, the quest for either European identity or the limits of EU enlargement becomes more and more important. In the opening of the article, the author commences to scrutinize upon what impact civilizations as such exert on the processes of European integration, disintegration, and international conflicts.The author goes intimate with a widely-discussed theory of Samuel P. Huntington - "The Clash of Civilizations" - where this scholar defines it to be civilization-based identity which in the contemporary world determines the framework for integration, disintegration, and international conflicts. Accordingly, in this sense, in post-modern European politics, religion becomes the most effective element of socialization and individualization of a person; it may forge both integration and, likewise, stipulate severe conflicts between the people who belong to separate civilizations.The strengthening of the European identity is bound to the simultaneous emergence of other equal and competitive civilizations. In a historical sense, the processes of European integration were essentially shaped by the inter-relationship that developed between Islam and Orthodox civilizations, on one hand, and Western Christianity, on the other. Lithuania's foreign policy may serve to be a pattern illustrating the significance of civilizations' factors in nowadays international relations and politics.
Keywords: -